Residual strains and morphometry in the human esophagus: Dependence on location, age, and gender - Sokolis, Dimitrios P.; Papadodima, Stavroula A.; Manopoulos, Christos (Journal of biomechanics, 2025)
The esophagus is a multi-layered organ that transports food to the stomach. While extensive biomechanical data exist for animal esophagi, human data remain limited. To address this, we analyzed residual deformations and zero-stress configurations in esophageal tissue from twenty-one cadavers (aged 21-84). Rings were photographed from fifteen equidistant locations before and after radial cutting and dissection into mucosa-submucosa and muscle layers. Image analysis revealed that the opening angles of the intact wall and muscle—slightly greater for the latter—did not vary significantly along the esophagus (p > 0.05 across age groups and genders). Conversely, the mucosa-submucosa had a larger opening angle, increasing along the esophagus (p < 0.05 in young subjects and both genders). Residual strains released by radial cutting and layer separation showed no anatomical position dependence (p > 0.05). The no-load internal circumference remained age-independent (p > 0.05 at all locations), while intact-wall thickness increased from young to middle-aged subjects due to mucosa-submucosa expansion (p < 0.05 in the upper half). No significant muscle growth occurred with age. This correlated with a rise in intact-wall opening angle between those age groups (p < 0.05 at the same sites), driven by more compressive internal residual strain (p < 0.05 near mid-esophagus). Age-related variations in layer-specific opening angles and residual strains were minimal (p > 0.05 in most locations). Males had wider, thicker esophagi (p < 0.05 in the upper half), but gender had no significant effect on opening angles and residual strains. This database provides new insights into the residual strains of the human esophagus and enhances computational simulations of transport and clinical interventions.